Perancangan Produk Interior Multifungsi Dan Adjustable Untuk Produk Pakaian, Sepatu Dan Tas - Regina Harijono; Grace Mulyono (Intra, 2019)
Online shop business is currently booming and very popular among many people. Many of them that have just started or even opened businesses for a long time often attend bazaars / exhibitions to increase their sales or to introduce their products. Few of the tenants who join the event bring their own additional furniture to enhance the visual of the booth as well as an additional display for the products. But usually thisfurniture does not match the size of the booth because each exhibition event has a different booth size. Therefore, a supporting facility that can be used repeatedly with an attractive and efficient design is needed. By the concept of adjustable and multifunctional design this product is made. The design aims to create products that can be adjusted in size and can also accommodate product display systems and to be easily used by tenants in the events. With this design it is expected to be a solution for participants or business people in participating in various exhibition activities.